Secondary metabolites, antioxidant and antiproliferative activities of dioscorea bulbifera leaf collected from Endau Rompin, Johor, Malaysia - Mainasara, Muhammad Murtala; Abu Bakar, Mohd Fadzelly; Md Akim, Abdah; Linatoc, Alona C; Abu Bakar, Fazleen Izzany; Ranneh, Yazan K. H. (Hindawi, 2021)
Breast cancer is among the most commonly diagnosed cancer and the leading cause of cancer-related death among women globally. Malaysia is a country that is rich in medicinal plant species. Hence, this research aims to explore the secondary metabolites, antioxidant, and antiproliferative activities of Dioscorea bulbifera leaf collected from Endau Rompin, Johor, Malaysia. Antioxidant activity was assessed using 2,2-diphenyl-1-picrylhydrazyl (DPPH), ferric reducing antioxidant power (FRAP), and 2,2′-azino-bis-3-ethylbenzthiazoline-6-sulphonic acid (ABTS) assays, while the cytotoxicity of D. bulbifera on MDA-MB-231 and MCF-7 breast cancer cell lines was tested using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay. Cell cycle analysis and apoptosis were assessed using flow cytometry analysis. Phytochemical profiling was conducted using gas chromatography-mass spectrometry (GC-MS). Results showed that methanol extract had the highest antioxidant activity in DPPH, FRAP, and ABTS assays, followed by ethyl acetate and hexane extracts. D. bulbifera tested against MDA-MB-231 and MCF-7 cell lines showed a pronounced cytotoxic effect with IC50 values of 8.96 μg/mL, 6.88 μg/mL, and 3.27 μg/mL in MCF-7 and 14.29 μg/mL, 11.86 μg/mL, and 7.23 μg/mL in MDA-MB-231, respectively. Cell cycle analysis also indicated that D. bulbifera prompted apoptosis at various stages, and a significant decrease in viable cells was detected within 24 h and substantially improved after 48 h and 72 h of treatment. Phytochemical profiling of methanol extract revealed the presence of 39 metabolites such as acetic acid, n-hexadecanoic acid, acetin, hexadecanoate, 7-tetradecenal, phytol, octadecanoic acid, cholesterol, palmitic acid, and linolenate. Hence, these findings concluded that D. bulbifera extract has promising anticancer and natural antioxidant agents. However, further study is needed to isolate the bioactive compounds and validate the effectiveness of this extract in the In in vivo model.